Pemikiran Mohammed Arkoun Dalam Penafsiran Kontemporer - Misnawati Misnawati; Samsul Bahri; Muhammad Nuzul Abrar (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Mohammed Arkoun is a scholar who provides another breakthrough as an alternative in understanding the Qur'an, although he is not the first, who propose the Qur'an ѕahīh fī kulli zamān wa makān. This is idea has motivated comtemporer scholar deeply discuss on the Qur’anic discourse. Arkoun, who is a neo-modernist thinker, tried to suggest the hermeuneutic approach as a wayout solution in overcoming problems related to the methodology of interpreting the Qur'an. Some of his thoughts conveyed were contradictory to the thought of other Muslim figures. He is one og the thinkers who are in the path of "outside the line" that had been set by the previous scholars. The thinkers claimed that a new path needed to be taken in interpreting Qur’an in order to be relevance to the present time. This article aims to see how Arkoun thinks about the hermeneutics of the Qur'an and his understanding of the entity of the Qur'an. This paper uses library research with a descriptive analytical approach to obtain an overview of Arkoun's thoughts on contemporary interpretation. According to him, the Qur'an is a combination of oral tradition, speech or open substantive communication with a closed and formative system of writing, text, courpus. As an inclusive oral or utterance tradition, the Qur'an in essence can accept various forms of interpretation from various cross-disciplines.